2016
DOI: 10.18632/oncotarget.10345
|View full text |Cite
|
Sign up to set email alerts
|

miR-151-5p, targeting chromatin remodeler SMARCA5, as a marker for the BRCAness phenotype

Abstract: In recent years, the assessment of biomarkers useful for “precision medicine” has been a hot topic in research. The involvement of microRNAs in the pathogenesis of breast cancer has been highly investigated with the aim of being able to molecularly stratify this highly heterogeneous disease. Our aim was to identify microRNAs targeting DNA repair machinery, through Affymetrix GeneChip miRNA Arrays, in a cohort of BRCA-related and sporadic breast cancers. Moreover, we analyzed microRNA expression taking into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(39 reference statements)
0
19
1
Order By: Relevance
“…One breast cancer study had found that miR-361 was overexpressed in PARP1-upregulating BRCA -germline mutated and sporadic breast cancers. [39]. Another breast cancer study that examined 28 breast cancer samples observed that miR-361 upregulation was indicative of metastatic breast cancer, but an association with metastasis does not imply a statistically significant association with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…One breast cancer study had found that miR-361 was overexpressed in PARP1-upregulating BRCA -germline mutated and sporadic breast cancers. [39]. Another breast cancer study that examined 28 breast cancer samples observed that miR-361 upregulation was indicative of metastatic breast cancer, but an association with metastasis does not imply a statistically significant association with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, the attention has been drawn to molecular aberrations underlying DNA repair damage dysfunction in order to better select patients treatable with PARPi. A recent study showed the possibility of considering the overexpression of PARP1 and miR-151-5p as biomarkers useful to correctly treat sporadic breast cancers with PARPi [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus miR-664b-5p has an important role in the regulation of PARP inhibitors to increase chemosensitivity by targeting CCNE2 in BRCA1 not-mutated TNBC ( 93 ). Furthermore, an interesting mechanism involving miR-151-5p and its target SMARCA5, an ISWI family member with an important role in DSB repair ( 94 ), has been proposed. Indeed, Tommasi et al reported the possibility of considering the overexpression of PARP1 and miR-151-5p as predictive biomarkers, useful to correctly select sporadic breast cancers for treatment with PARP inhibitors.…”
Section: Micrornas Regulate Dna Repair Genes and Parp Inhibitor Respomentioning
confidence: 99%